Fertilization and nutrient demand NPK of Swietenia macrophylla King and Cedrela odorata L. in development - Pérez-Camacho, Pedro; Obrador-Olán, José Jesús; Castelán-Estrada, Mepivoseth; Carrillo-Avila, Eugenio; Sol-Sanchez, Angel; Córdova-Sánchez, Alberto; Juárez-López, José Francisco (Ecosistemas y Recursos Agropecuarios, 2024)
Mahogany and cedar are native species of tropical America and are considered the most valuable tropical hardwoods in the world. Therefore, forest plantations have been established on a commercial scale, giving them a sustainable silvicultural management, being fertilization one of the most important practices. The objective of this work was to evaluate the effect of four doses of fertilization on the growth of early-stage mahogany and cedar in an acid savanna soil, as well as to determine the NPK nutrient demand of each species. Eight fertilization treatments were tested on the two species. The variables studied were total height and stem diameter, and measurements were taken during 10 months. To estimate nutrient demand, four complete trees were sampled and NPK concentration was determined in each tissue (leaf, stem and root). The results show that cedar presented greater growth in height and diameter. In the height variable in the cedar species, it was the one that showed significant statistical differences, being the treatment 17-17-60 with the amounts of 35 and 50 g with an increase of 177 cm. The amount of NPK nutrient demanded by both species presented a relationship in the following order N>K>P. The greatest extraction of N, P and K is carried out by the stem and to a lesser extent by the root. And in the case of the highest concentration of nutrient is found in the leaves. Cedar showed higher nutrient demand and better exploration of the rhizosphere tan mahogany.